Analysis of Elastohydronamic Lubrication of the Roller Enveloping End Face Engagement Worm Drive - Xiaolong Wang (Jixie chuandong)
To study the lubrication performance of roller enveloping end face engagement worm drive， the elastohydrodynamic lubrication （EHL） model is established based on meshing theory of roller enveloping end face engagement worm drive and the theory of EHL. Based on calculation formula of approximate film thickness and film thickness ratio in every lubrication condition area， the simulation is conducted using Matlab software， and the time-domain distribution of lubrication condition， minimum film thickness and film thickness ratio are analyzed， it can be concluded as that this transmission pair has better lubrication performance. Finally， the influences of roller radius R and orifice coefficient k on lubrication performance of the transmission pair are analyzed. The results show that the roller radius R should not too bigger， orifice coefficient k should not too smaller， for effectively improving the lubrication performance of the roller enveloping end face engagement worm drive．